Jørgen Elbek: Grundtvigs atten prøveår - Albeck, Gustav (Grundtvig-studier, 1974)
Jørgen Elbek: Grundtvigs atten prøveår. Published by G. M. T., 1974 Reviewed by Gustav Albeck Jorgen Elbek’s monograph is a very concentrated analysis of Grundtvig’s development during the period from 1805 to 1823/24, when he wrote his major poetical work Nyaars-Morgen. The monograph is based on an intimate knowledge of the works of Grundtvig and the literature on him. In his condensed account the author reasons both logically and subjectively at the same time, which does not make it easy for the reader to persuade himself of the necessity for the many different phases of the analysis.Many points invite contradiction and the conclusion, in which the author paves the way for a massive depreciation of Grundtvig’s literary production after 1824, will hardly pass unchallenged.All things considered, this is, however, a piece of work that contains original and stimulating thoughts and which will give experts on Grundtvig much to ponder over.